Análise do Sistema Agroindustrial (SAI) do biodiesel no Paraná com enfoque na nova economia institucional - Graef, Nelinho Davi (2012)
This study examined and prospected the potential and limitations of the agribusiness of biodiesel in Parana, from the concepts of New Institutional Economics. For this, we used the exploratory and descriptive research on ends. The means we use has been made of bibliographical and documentary research and qualitative methods. The content analysis method was used to observe the results, performing a comparison between the theoretical elements and information gathered in surveys. The results suggest the major potential SAI biodiesel Paraná: The state has the second largest consumer market for biodiesel and is geographically located near the largest market that is São Paulo, the state's second largest soybean producer in Brazil; the system includes an organizational environment solid with important support and research organizations, biodiesel has two important differences as the marketing contribution to ensuring the sovereignty and energy security and environmental benefits offered. The main bottlenecks were prospected: So far not found a raw material that is technologically and economically feasible to produce biodiesel, the industrial processing of soybeans, raw material most used in the production of biodiesel is higher in Paraná that the production thereof; other raw materials does not guarantee production scale for the production of biodiesel, the production technology is not stabilized and presents a set of problems that need to be resolved, the price of biodiesel cannot be competitive against the diesel fuel, requiring government subsidies for the continuation of the program, the sale of oil these raw materials for other uses has a higher valuation. Thus, the bottlenecks found in the SAI biodiesel Parana has been outstanding on the potential, there were preventing growth and development of the agribusiness biodiesel in Paraná.